دور عمليات إدارة المعرفة في تفعيل التطوير التنظيمي دراسة حالة بالمديرية العملية لإتصالات الجزائر الأغواط - قزم فطيمة; عبد العالي خديجة أم البنين; نعيجات عبد الحميد (جامعة عمار ثليجي الاغواط, 2022)
In this study, we discussed the role of knowledge management processes in the operationalization of organizational development. In order to achieve the objectives of the study, we used an identification of the view of the staff of an institution on the nature of the relationship between knowledge management processes and organizational development. (55) We relied on data analysis on SPSS SMART statistical analysis with a view to studying the different relationships between the studied variables. The results of the statistical analysis produced a set of results, namely, the statistical impact of knowledge management processes on the organizational development of the Algiers Communications Directorate at the morale level (0.05=α). The study also found that there were no statistically significant differences at the same level of morale and the same variables of the study's personal data model in individuals of the sample studied: sex, age, scientific level, functional level, and duration of experience.